Laparoscopic versus Open Surgery in Lateral Lymph Node Dissection for Advanced Rectal Cancer: A Meta-Analysis - Manzhao Ouyang; Tianyou Liao; Yan Lu; Leilei Deng; Zhentao Luo; Jinhao Wu; Yongle Ju; Xueqing Yao (Gastroenterology Research and Practice)
Aim. To compare the clinical efficacies between laparoscopic and conventional open surgery in lateral lymph node dissection (LLND) for advanced rectal cancer. Methods. We comprehensively searched PubMed, Embase, Cochrane Library, CNKI, and Wanfang Data and performed a cumulative meta-analysis. According to inclusion criteria and exclusion criteria, all eligible randomized controlled trials (RCTs) or retrospective or prospective comparative studies assessing the two techniques were included, and then a meta-analysis was performed by using RevMan 5.3 software to assess the difference in clinical and oncological outcomes between the two treatment approaches. Results. Eight studies involving a total of 892 patients were finally selected, with 394 cases in the laparoscopic surgery group and 498 cases in the traditional open surgery group. Compared with the traditional open group, the laparoscopic group had a longer operative time (WMD=81.56, 95% CI (2.09, 142.03), P=0.008), but less intraoperative blood loss (WMD=−452.18, 95% CI (-652.23, -252.13), P<0.00001), shorter postoperative hospital stay (WMD=−5.30, 95% CI (-8.42, -2.18), P=0.0009), and higher R0 resection rate (OR=2.17, 95% CI (1.14, 4.15), P=0.02). There was no significant difference in the incidence of surgical complications between the two groups (OR=0.52, 95% CI (0.26, 1.07), P=0.08). Lateral lymph node harvest, lateral lymph node metastasis, local recurrence, 3-year overall survival, and 3-year disease-free survival did not differ significantly between the two approaches (P>0.05). Conclusion. Laparoscopic LLND has a similar efficacy in oncological outcomes and postoperative complications to the conventional open surgery, with the advantages of reduced intraoperative blood loss, shorter postoperative hospital stay, and higher R0 resection rate, and tumor radical cure is similar to traditional open surgery. Laparoscopic LLND is a safe and feasible surgical approach, and it may be used as a standard procedure in LLND for advanced rectal cancer.